2021
DOI: 10.1177/03635465211042014
|View full text |Cite
|
Sign up to set email alerts
|

Securing Transplanted Meniscal Allografts Using Bone Plugs Results in Lower Risks of Graft Failure and Reoperations: A Meta-analysis

Abstract: Background: Meniscal allograft transplant (MAT) is an important treatment option for young patients with deficient menisci; however, there is a lack of consensus on the optimal method of allograft fixation. Hypothesis: The various methods of MAT fixation have measurable and significant differences in outcomes. Study Design: Meta-analysis; Level of evidence, 4. Methods: A single-arm meta-analysis of studies reporting graft failure, reoperations, and other clinical outcomes after MAT was performed. Studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…The present study reported survival rates of 94% at 5 years and 89% at 10 years, rates that are comparable with other large case series that involved bone plug fixation techniques. 12 , 17 This finding contrasts the results of a recent meta-analysis by Ow et al, 21 who found a lower reoperation rate with the bone plug fixation technique. Interestingly, those investigators did not specify whether the reoperations were related to the MAT procedure, and the rate of second surgery was not weighted based on the percentage of concurrent procedures.…”
Section: Discussionmentioning
confidence: 86%
“…The present study reported survival rates of 94% at 5 years and 89% at 10 years, rates that are comparable with other large case series that involved bone plug fixation techniques. 12 , 17 This finding contrasts the results of a recent meta-analysis by Ow et al, 21 who found a lower reoperation rate with the bone plug fixation technique. Interestingly, those investigators did not specify whether the reoperations were related to the MAT procedure, and the rate of second surgery was not weighted based on the percentage of concurrent procedures.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, the rates of reoperation were the lowest in the bone plug group (5.2%), followed by the suture-only group (13.4%) and the bone bridge group (32.6%). There were no significant differences in MRI-assessed graft extrusion between groups 10 .…”
Section: Meniscusmentioning
confidence: 71%
“…The ideal surgical technique for securing meniscal allografts remains controversial. In a meta-analysis of 36 studies, Ow et al 10 assessed the outcomes of meniscal allograft transplantation in 2,604 patients by comparing sutures only (24.7%), bone plugs (43.5%), or bone blocks (31.6%) for fixation. Graft failure, defined as requiring revision meniscal allograft transplantation, conversion to joint arthroplasty, or allograft removal, was the lowest in the bone plug group (6.2%), followed by the suture-only group (6.9%), and was the greatest in the bone bridge group (9.3%).…”
Section: Meniscusmentioning
confidence: 99%
“…Future applications should investigate transosseous suture fixation, bone anchors or bone plug fixation, which seems to be the most efficient fixation method. 25,26 At the 18-month radiographic follow-up, stable fixation of the PSI with evidence of bony incorporation was present. Previous studies in a sheep model using similar implants showed bone-to-implant contact already at 6 months.…”
Section: Discussionmentioning
confidence: 98%
“…Future applications should investigate transosseous suture fixation, bone anchors or bone plug fixation, which seems to be the most efficient fixation method. 25 26…”
Section: Discussionmentioning
confidence: 99%